Business (not) for peace: Incentives and disincentives for corporate engagement on good governance and peaceful development in the African context. Issue 2 (3rd April 2019) - Ganson, Brian
ABSTRACT: European policy towards Africa assumes a peace-positive role for the private sector in developing countries. Conflicting evidence from fragile and conflict affected states, however, underlies a stark debate over business, peace, development, and extractives sector governance. This study draws from deep dives into about a dozen fragile and conflict affected contexts to add nuance to this conversation and inform future policy. It examines in turn three factors that rose to prominence in that research: the political economy shaping the private sector; disincentives for the private sector to engage in peacebuilding and statebuilding; and practical limitations of companies as peacebuilding actors. These factors help to explain the exceptional nature of those businesses that engage decisively for good governance and peace. Unpacking these factors may also open new entry points for shaping a private sector more likely to become an engaged and effective peacebuilding and statebuilding partner in extractives sector governance.